Monitora Tocantins: desenvolvimento do aplicativo para análises dos impactos da Covid-19 na região do Baixo Tocantins - WANZELER, Natanael Garcia (2025)
With the propagation of the Coronavirus pandemic, the two hospitals in the city of Cametá, in Baixo Tocantins, as well as the health centers, became full, due to the cases, without there being any care for the entire sick population that presented in the emergency rooms of these hospitals. In light of this problem, it was necessary to develop an application to monitor COVID-19 cases in the city, to provide guidance of care and prevention of the virus and to map the places with high levels of contamination. In order to achieve this, the Monitora Tocantins application was created, with the objective of monitoring the symptoms of the disease through the data collected by the form present in the application. The set of activities that granted achieving the project objectives was based on an applied approach aiming to fulfill the main stages of the development process that involve the gathering of requirements, which serves to detail the functionality of the application; the choice of the tools that will be used in the creation of the application is another important step; moreover, the elaboration of the use case diagram is an essential part of understanding what was not clear in the requirements; as well as the logical model that is meant to plan which data will be stored in the application. Therefore, the Monitora Tocantins multiplatform application is the main result of the execution of the specific objectives necessary to achieve this general objective. The expected results were attained with the completion of the development and the stability of the application.